Relationship Between Repeat Visit Interest And Patient Satisfaction In The Outpatient Unit At Grha Permata Ibu Hospital In 2024 - Salsabila Azzahra; Desy Kartika Ningsih; Oci Etri Nursanty (Jurnal EduHealth, 2024)
Hospitals should focus more on patient satisfaction as a way to gain and maintain market share, maintain patient loyalty, and attract new customers or patients. Quality service ensures patient satisfaction, which ultimately makes patients voluntarily utilize or are willing to return to the hospital and voluntarily recommend the hospital's services to others. The purpose of this study was to determine the relationship between the intention of revisiting and patient satisfaction in the outpatient unit at the Grha Permata Ibu Hospital. This study is a quantitative study with a cross-sectional approach. Sampling in this study used random sampling of 100 respondents. The results showed that there was a relationship between the intention of revisiting (p = 0.000) and patient satisfaction. The conclusion of this study is that there is a significant relationship between the intention of revisiting and patient satisfaction in the outpatient unit at the Grha Permata Ibu Hospital with ap value <0.05.